Creation tracks and trade winds : Groote Eylandt bark paintings : from the University of Melbourne Art Collection. - University of Melbourne; Bosse, Joanna; Ian Potter Museum of Art. ([Melbourne] : Ian Potter Museum of Art, 2006)
Exhibition catalogue which includes an analysis of many of the bark paintings, from the 1940s, in the exhibition including subjects and painting techniques; includes brief history of Groote Eylandt and the people's relationships with Macassans.
Cover title.
Curator: Joanna Bosse.
Exhibition held at the Ian Potter Museum of Art from 23 September 2006 to 21 January 2007.
Keywords: University of Melbourne -- Exhibitions; Bark painting -- Northern Territory -- Groote Eylandt -- Exhibitions; Art, Aboriginal Australian -- Northern Territory -- Groote Eylandt -- Exhibitions; Art - Exhibitions; Settlement and contacts - Macassans and Indonesians; Art - Painting - Bark; Art - Catalogues; Groote Eylandt (NT Gulf Islands SD53-07, SD53-08)